ANALISIS PENGARUH TOP MANAGEMENT COMMITMENT PADA HOTEL BUDGET DI SURABAYA JATIM - Cahyo Iriawan (Jurnal Penelitian Rumpun Ilmu Teknik, 2022)
Businesses worldwide are going rapidly nowadays. Almost all business sectors are facing this situation, and trying to find strategics moves to keep survive and grow. In hospitality industry this situation are also force them to keep evolve and change to find better strategies to growth. Role of Top Management are need to strive in business situation that getting tight. This study is using variable Top Management Commitment, Supplier Relationship Management, and Supplier Performance. By conducting a survey to 80 managers in the budget hotels which located in Suarabaya and using smartPLS to process all data that needed. The result of this study is shown that Top Management Commitment can affect Supplier Performance and also Supplier Relationship Management. It shows that Commitment from top management can help to keep and embrace relationship that may not too fine in the past. By keep improve the new ways and find an understanding by buyer and suppliers can easily to increase not only trust by two sides, but also business growth for each others.